Targeting fibroblast growth factor 19 in liver disease: a potential biomarker and therapeutic target. (May 2015) - Liu, Wen-Yue; Xie, Dong-Mei; Zhu, Gui-Qi; Huang, Gui-Qian; Lin, Yi-Qian; Wang, Li-Ren; Shi, Ke-Qing; Hu, Bin; Braddock, Martin; Chen, Yong-Ping; Zheng, Ming-Hua
<x xml:space="preserve">Abstract</x> Introduction: Fibroblast growth factor 19 (FGF19) is a member of the hormone-like FGF family and has activity as an ileum-derived postprandial hormone. It shares high binding affinity with β-Klotho and together with the FGF receptor (FGFR) 4, is predominantly targeted to the liver. The main function of FGF19 in metabolism is the negative control of bile acid synthesis, promotion of glycogen synthesis, lipid metabolism and protein synthesis. Areas covered: Drawing on in vitro and in vivo studies, this review discusses FGF19 and some underlying mechanisms of action of FGF19 as an endocrine hormone in several liver diseases. The molecular pathway of the FGF19-FGFR4 axis in non-alcoholic liver disease and hepatocellular carcinoma are discussed. Furthermore, definition of function and pharmacological effects of FGF19 for liver disease are also presented. Expert opinion: A series of studies have highlighted a crucial role of FGF19 in liver disease. However, the conclusions of these studies are partly paradoxical and controversial. An understanding of the underlying biological mechanisms which may explain inconsistent findings is especially important for consideration of potential biomarker strategies and an exploration of the putative therapeutic efficacy of FGF19 for human liver disease.